Penggunaan Anggaran Pendapatan dan Belanja Negara (APBN) dalam Pelaksanaan Pemilihan Umum Ulang - I Kadek Andika Setiawan; I Gusti Bagus Suryawan; I Wayan Arthanaya (Warmadewa Press, 2021)
A failed general election will result in a re-election and will certainly require additional budget. The purpose of this research is to find out the mechanism for the implementation of the re-election and to analyze the use of the State Revenue and Expenditure Budget in the implementation of the re-election. The research method used is normative legal research with a statutory approach and a conceptual approach. The results of this study indicate that the mechanism for implementing the re-election is a dispute over the results of the disputed General Election, by presidential candidates and members of the legislative candidates through the Constitutional Court decision. The mechanism for the provision of funds from the State Revenue and Expenditure Budget in the implementation of the re-General Election is the submission of additional costs by the General Election Commission to the Budget Institution and the Budget Department to revise the budget for the implementation of General Elections that are undergoing re-election.